Physiological responses in relation to robotic prostatectomy - Chong, Kok Wah; Salihan, Safuraa (Universiti Putra Malaysia, 2023)
Learning physiological responses through clinical application provides a meaningful experience that engraves itself in one’s mind forever. Robotic prostatectomy requires a patient to be positioned in a steep Trendelenburg, and this is associated with many physiological responses that involve the cardiovascular, respiratory, and central nervous system. Understanding the physiological responses during the robotic prostatectomy provides vital intraoperative monitoring and ensures the patient’s safety.